INCREASE IN CANDIDA PARAPSILOSIS CANDIDEMIA IN CANCER PATIENTS - Mingyue Sun; Chunguang Chen; weiqiang xiao; yanmin Chang; cailin Liu; Qingxia Xu (Mediterranean Journal of Hematology and Infectious Diseases)
Background: This study aimed to identify the risk factors of candidemia and asses possible clinically significant differences between Candida parapsilosis and other candida species among cancer patients.